2022
DOI: 10.1186/s13098-022-00843-8
|View full text |Cite
|
Sign up to set email alerts
|

The 2021–2022 position of Brazilian Diabetes Society on diabetic kidney disease (DKD) management: an evidence-based guideline to clinical practice. Screening and treatment of hyperglycemia, arterial hypertension, and dyslipidemia in the patient with DKD

Abstract: Background Diabetic kidney disease is the leading cause of end-stage renal disease and is associated with increased morbidity and mortality. This review is an authorized literal translation of part of the Brazilian Diabetes Society (SBD) Guidelines 2021–2022. This evidence-based guideline provides guidance on the correct management of Diabetic Kidney Disease (DKD) in clinical practice. Methods The methodology was published elsewhere in previous SBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 143 publications
0
4
0
4
Order By: Relevance
“…RAAS lowering with angiotensin-converting enzyme inhibitors (ACEi) or angiotensin receptor blockers (ARBs) is the first-line treatment for the clinical management of DKD [ 29 ]. GLP-1 receptor agonists have been added to the treatment toolkit because of their well-established benefits for kidney protection and patient survival [ 30 ]. Evidence from cardiovascular outcome trials using SGLT-2 inhibitors strongly suggested that these drugs, in addition to standard-of-care therapy, significantly slowed the course of CKD in people with diabetes mellitus [ 31 ].…”
Section: Reviewmentioning
confidence: 99%
“…RAAS lowering with angiotensin-converting enzyme inhibitors (ACEi) or angiotensin receptor blockers (ARBs) is the first-line treatment for the clinical management of DKD [ 29 ]. GLP-1 receptor agonists have been added to the treatment toolkit because of their well-established benefits for kidney protection and patient survival [ 30 ]. Evidence from cardiovascular outcome trials using SGLT-2 inhibitors strongly suggested that these drugs, in addition to standard-of-care therapy, significantly slowed the course of CKD in people with diabetes mellitus [ 31 ].…”
Section: Reviewmentioning
confidence: 99%
“…El tratamiento intensivo de la PA en pacientes con ERD es parte del cuidado usual recomendado actualmente por las diferentes guías de manejo dado su beneficio en retrasar la progresión de la ERD y reducción de eventos cardiovasculares adversos (6). Tempranamente en la historia del control de la PA en pacientes con ERD se ha demostrado los beneficios de su reducción, el primer bloqueador del sistema RAAS utilizado en pacientes con HTA y DM fue el captopril el cual logró demostrar que el control de la presión arterial (PA) tendría beneficios en la reducción de albuminuria (8).…”
Section: Tratamiento De La Hipertensión En Pacientes Con Erdunclassified
“…Dentro de la estrategia de tratamiento y gestión de riesgo en pacientes con enfermedad renal diabética, la identificación de factores de riesgo modificables y potencialmente modificables es fundamental para guiar estrategias de tratamiento (6). En este sentido los factores de riesgo para progresión de la ERD incluyen hiperglicemia, hipertensión arterial, albuminuria, dislipidemia, tabaquismo, obesidad, dieta inadecuada y estilos de vida sedentarios (6,7). Por ello, además de plantearnos una meta de presión arterial se buscará impactar sobre componentes adicionales del riesgo cardiovascular y progresión de la ERD (6,7).…”
Section: Introductionunclassified
See 2 more Smart Citations